PERANCANGAN PESAWAT UAV KAMIKAZE GARUDA WISANGGENI - Anisa Nurpitriani, Gifani; Putra An'nur, Alif (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Developments in aviation technology have expanded the use of Unmanned Aerial Vehicles (UAVs), particularly for operations requiring rapid response and long-range capabilities. Fixed-wing UAVs are a preferred choice due to their superior flight stability, energy efficiency, and longer endurance compared to multirotor types. One specific variant, the kamikaze UAV or loitering munition, requires efficient aerodynamic design, high structural integrity, and guaranteed operational reliability. This study aims to design the